Loyalist Mobilization and Cross-Border Violence in Rural Ulster, 1972-1974 - Burke, Edward (Terrorism and political violence, 2022)
This article argues that, at a tactical level, loyalist terrorism in the Irish border region between 1972 and 1974 worked. Cross-border attacks including bombings in Irish towns prompted the Irish government to reinforce security along the border—a long-standing loyalist demand. The loyalist campaign led to the IRA embarking on an effort to punish those who were believed to have passed information to loyalists, resulting in the killing of an Irish Protestant senator and widespread condemnation of the organization in the Republic of Ireland. However, short-term gains were outweighed by a growing perception among nationalists that the British state tolerated or even colluded in such attacks, undermining the British Army’s campaign to gain trust (and information) within the Catholic population of Northern Ireland. The article also contends that middle-class loyalists played an important role in mobilizing and equipping loyalist paramilitary organizations. It concludes that the British Army showed an excessive tolerance of loyalists with political capital or ties to the security forces, despite evidence that such individuals were directly supporting the activities of loyalist paramilitaries.